Low-coordinate iridium NHC complexes derived from selective and reversible C–H bond activation of fluoroarenes1. Issue 21 (14th March 2015) - Hauser, Simone A.; Prokes, Ivan; Chaplin, Adrian B.
<x xml:space="preserve">Abstract</x> A reactive iridium(i) fragment supported by conformationally rigid NHC ligands undergoes mild and reversible C–H bond activation of simple fluoroarenes.